Externally validated nomogram for predicting short-term pregnancy outcome of singleton pregnancies with fetal growth restriction (FGR) - Yang Li; Xiaohong Zhang; Junshu Xie; Fufen Yin; Mingrui Jin; Yujing Li; Xiuju Yin (Gynecology and Obstetrics Clinical Medicine)
Objective This study aimed at developing an available predictive model of singleton pregnancies with fetal growth restriction (FGR) for accurate and individualised prognosis assessment.Methods The prediction nomogram was developed by using multivariable Cox regression with data for 301 singleton FGR pregnancies at Peking University People’s Hospital. External validation was performed in 321 eligible singleton FGR pregnancies at the Affiliated Hospital of Qingdao University.Results Absent umbilical arterial flow, fetal anomaly, history of abnormal pregnancy, non-cephalic presentation and history of caesarean section were independent prognostic factors for adverse perinatal outcomes in singleton FGR pregnancies in the training set. In the training cohort of the internal validation set, the nomogram estimated pregnancy prognosis of FGR singleton pregnancies based on these five variables, with a concordance index (C-index) of 0.859 (95% CI: 0.81 to 0.90) for predicting termination of pregnancy (TOP), which included intrauterine fetal death and therapeutic lethal induction, with a C-index of 0.92 (95% CI: 0.86 to 0.98) for predicting stillbirth, and a C-index of 0.87 (95% CI: 0.83 to 0.92) for predicting therapeutic lethal induction with indications. Encouragingly, consistent results were observed in the external validation set, with a C-index of 0.776 (95% CI: 0.71 to 0.84) for predicting TOP, which included intrauterine fetal death and therapeutic lethal induction, with a C-index of 0.773 (95% CI: 0.70 to 0.84) for predicting stillbirth, and a C-index of 0.776 (95% CI: 0.70 to 0.85) for predicting therapeutic lethal induction with indications. Furthermore, the calibrations of the nomograms predicting the 28th and 34th TOP-free gestation week strongly corresponded to the actual survival outcome.Conclusion This prediction model may help clinicians in decision-making for singleton pregnancies with FGR, especially for patients with a single abnormal umbilical arterial flow or fetal anomaly, without induced labour indications for these abnormalities.